Effect of Antituberculosis, (Rifampicin & Isoniazide) on Female Reproductive System Performance in Adult Rats - AL-Chalaby, A. S. (Kufa Journal For Veterinary Medical Sciences, 2012)
A study was made of the effects of anti-tuberculosis agents (Rifampicin, Isoniazide) on female reproductive performance, (30) Adult female albino rats were used, While ( 12 ) were treated orally with Rifampicin ( 50 mg/kg ) and Isoniazide ( 25 mg/kg ) for 60 days , and reversibility of the induced effects by withdrawal of the treatment for 30 days were also investigated , as well as 6 rats served as control , Results reveled that absolute and relative weight of uterus and spleen are significantly non changed , while absolute and relative weight of the ovary decreased significantly , relative liver weight increased significantly , while Isoniazide cause significantly increased in heart weight , compared to control group, The withdrawal of Rifampicin and Isoniazide for 30 days brought about on complete recovery , Fertility was reduced significantly after both Rifampicin and Isoniazide administration for 60 days , Hence the effects of Rifampicin and Isoniazide are transient and reversible.